Pertumbuhan dan Hasil Jagung yang Dipupuk N, P, dan K pada Tanah Vertisol Isimu Utara Kabupaten Gorontalo - . Nurdin; Purnamaningsuh Maspeke; Zulzain Ilahude; Fauzan Zakaria (JOURNAL OF TROPICAL SOILS, 2009)
The fertilizer availability as source of N, P, and K nutrient where plant responsif  was difficult found by farmer. Thefore, It was needed information about nutrient availability in soil properties to know nutrient deficiency of its by maize as plant indicator. The  objective of this research was to study the respons of  N, P, and K fertilizers and the best combination of it on the growth and yield of Maize. The research conducted at Udic Pellusterts in North Isimu Tibawa District of Gorontalo Regency. The experi- mental design was following random block design that consist of 5 treatments with 3 replications. The result of this research showing that minus N, P, and K fertilizers have a significantly effect on plant age polination, the percentage of height stem of  an ear of corn to plant height and dry straw weight but did not have significantly effect on plant height and the weigh of one hundred grain of Maize. To improve the growth and yield of Maize using fertilizing without P treatment were 250 kg Urea ha-1 and 75 kg KCl ha-1 or completely dosage were 250 kg Urea ha-1, 100 kg TSP ha-1 and 75 kg KCl ha-1 as the best fertilizers combination.